Occurrence of Uranium in Groundwater Along the Lithological Contacts in Central Tamilnadu, India: An Isotope Hydrogeochemical Perspective - Adithya, V.; Chidambaram, S.; Keesari, T.; Mohokar, H.; Prasanna, Mohan Viswanathan (2017)
© 2017 Springer Science+Business Media B.V., part of Springer Nature Groundwater contributes to the highest exposure level of naturally occurring uranium (U) to biosphere, and hence, the source and concentration of uranium in groundwater needs to be monitored periodically. In the present study, groundwaters from different lithologic locations were collected and measured for uranium concentration and major ions in order to establish any possible link with the lithology on the uranium distribution in central parts of Tamil Nadu, South India. About 11% of the samples contain U in excess of the permissible limit of WHO (Guidelines for drinking-water quality, WHO, Geneva, 2011), and the contamination was limited to mostly hard rock terrain, which is granitic in nature. The correlations among U, major ions, and environmental isotopes were studied to understand the mechanism governing uranium dissolution and transport in groundwater of this region. Observations lead us to infer that the older water with near-neutral pH and oxidizing condition contains higher dissolved U compared with relatively young groundwater. The results also reflect the possible health risk to the local population through long-term consumption of uranium-containing groundwater without any pretreatment.